2020
DOI: 10.1097/sap.0000000000002517
|View full text |Cite
|
Sign up to set email alerts
|

Fractionated Ablative Carbon Dioxide Laser Therapy Decreases Ultrasound Thickness of Hypertrophic Burn Scar

Abstract: Introduction Carbon dioxide (CO2) laser treatment is routinely used to treat hypertrophic burn scars (HBS). Although prior research has documented subjective improvement in HBS after treatment, there is little data evaluating objective changes in scar characteristics after therapy. The aim of our process improvement project was to evaluate changes to scar thickness (ST) using high-frequency ultrasound in patients with HBS undergoing CO2 laser therapy. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Some studies have found a benefit to laser therapy after just one treatment. 20,22,23 In a process improvement initiative led by our group, 21 patients with HTBS treated with CO 2 laser experienced improvement in ST with the greatest im-provement seen after the first treatment for both thin and thick scars ( P = 0.061 and 0.022, respectively). 23 Hultman et al 22 conducted a prospective, before-after cohort study of 147 patients receiving PDL, CO 2 , intense pulsed light, or Alexandrite laser treatments, and found that Vancouver Scar Scale (VSS) and University of North Carolina "4P" Scar Scale both decreased significantly ( P < 0.0001, P < 0.0001, respectively) with the largest decrease occurring following the first laser session.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found a benefit to laser therapy after just one treatment. 20,22,23 In a process improvement initiative led by our group, 21 patients with HTBS treated with CO 2 laser experienced improvement in ST with the greatest im-provement seen after the first treatment for both thin and thick scars ( P = 0.061 and 0.022, respectively). 23 Hultman et al 22 conducted a prospective, before-after cohort study of 147 patients receiving PDL, CO 2 , intense pulsed light, or Alexandrite laser treatments, and found that Vancouver Scar Scale (VSS) and University of North Carolina "4P" Scar Scale both decreased significantly ( P < 0.0001, P < 0.0001, respectively) with the largest decrease occurring following the first laser session.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that fractional CO 2 laser treatments improve HS using selective photothermolysis, producing microthermal damage of almost the same density and depth 4 . Furthermore, some researchers have reported that fractional CO 2 laser treatment can soften and flatten the scar and reshape the collagen arrangement 24 . In addition, numerous clinical and preclinical studies have shown that fractional CO 2 laser therapy for HS is safe and effective with rare side effects 7 .…”
Section: Discussionmentioning
confidence: 99%
“…4 Furthermore, some researchers have reported that fractional CO 2 laser treatment can soften and flatten the scar and reshape the collagen arrangement. 24 In addition, numerous clinical and preclinical studies have shown that fractional CO 2 laser therapy for HS is safe and effective with rare side effects. 7 Regarding the molecular mechanism, fractional CO 2 laser treatments can regulate TGFβ, BMP-7, Fas, and other signaling pathways, inhibit TGF-β1 production, create microholes to replace collagen fibrils, and decrease the number of abnormal collagen fibers, thus improving HS.…”
Section: Fractional Co 2 Laser Combined With Btxa Injection Inhibited...mentioning
confidence: 99%
“…A further subgroup analysis was also performed which revealed that patients at the early stage could experience more significant improvement after the treatment of combined therapy. Ablative fractional CO 2 laser technology has been employed for many years; however, it is only in recent years that this technique has been applied to the treatment of hypertrophic scars (3,4,(13)(14)(15)(16)(17)(18)(19). Several case reports firstly reported the effectiveness of ablative fractional CO 2 laser treatment for hypertrophic scars (20,21), then Makboul et al enrolled 40 patients with hypertrophic scars and confirmed ablative fractional CO 2 laser treatment as a feasible management for hypertrophic scarring (22).…”
Section: Discussionmentioning
confidence: 99%
“…Hypertrophic scars caused by burns are also very common, and the injury to patients is greater due to the randomness and unpredictability of scar site. It has been reported that hypertrophic scar affects 32-72% of burn survivors based on patient age, wound infection, gender, and burn depth (4,5). The formation of hypertrophic scar can lead to unsightly appearance, restricted movement, psychological burden, and abnormal bodily sensations.…”
Section: Introductionmentioning
confidence: 99%